1995
DOI: 10.1111/j.1476-5381.1995.tb14977.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacology and distribution of human 5‐hydroxytryptamine2B (5‐HT2b) receptor gene products: comparison with 5‐HT2a and 5‐HT2c receptors

Abstract: 1 Full length clones of the human 5-HT2B receptor were isolated from human liver, kidney and pancreas. The cloned human 5-HT2B receptors had a high degree of homology (-80%) with the rat and mouse 5-HT2B receptors. 2 PCR amplification was used to determine the tissue distribution of human 5-HT2B receptor mRNA. mRNA encoding the 5-HT2B receptor was expressed with greatest abundance in human liver and kidney. Lower levels of expression were detected in cerebral cortex, whole brain, pancreas and spleen. Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
162
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(172 citation statements)
references
References 23 publications
9
162
1
Order By: Relevance
“…All data are 5-HT, 5-HT2B and 5-HT2c (see Fozard & Kalkman, 1994). usually higher (pKD-6.7-7.6: Hoyer et al, 1985;Herndon et al, 1992;Bonhaus et al, 1995) than for 5-HT2B receptors (pKD-5.5-6.7: Loric et al, 1992;Wainscott et al, 1993;Bonhaus et al, 1995) in a variety of species including man (Bonhaus et al, 1995). In cell lines derived from mouse teratocarcinoma, 5-HT2B receptors are expressed during differentiation that have even relatively high affinity for ketanserin (pKD-7.2-7.4, Loric et al, 1995).…”
Section: Effects Of Skandf 103829mentioning
confidence: 99%
“…All data are 5-HT, 5-HT2B and 5-HT2c (see Fozard & Kalkman, 1994). usually higher (pKD-6.7-7.6: Hoyer et al, 1985;Herndon et al, 1992;Bonhaus et al, 1995) than for 5-HT2B receptors (pKD-5.5-6.7: Loric et al, 1992;Wainscott et al, 1993;Bonhaus et al, 1995) in a variety of species including man (Bonhaus et al, 1995). In cell lines derived from mouse teratocarcinoma, 5-HT2B receptors are expressed during differentiation that have even relatively high affinity for ketanserin (pKD-7.2-7.4, Loric et al, 1995).…”
Section: Effects Of Skandf 103829mentioning
confidence: 99%
“…Some pharmacological properties of antagonistic compounds such as yohimbine relate this pharmacology to that of the 5-HT1B-1D subfamily. The group of T. Blackburn reported the synthesis of a first generation of selective antagonist, the SB200646A compound which possess high affinity for 5-HT2B and 5-HT2C but not 5-HT2A nor any other receptor tested [5]. This compound acts on hypolocomotion, hypophagia and anxiogenic paradigms [6].…”
Section: Introductionmentioning
confidence: 99%
“…ICP responses resulting from direct stimulation of the CN (20 Hz, 2.5 V, 1 ms pulse width) were similar 10 Bonhaus et al, 14 Bigoni et al 41 and Paiva et al 42 m-CPP induced intracavernous pressure responses ES Hayes and PG Adaikan amongst treatment groups and ranged from 27 AE 4 mmHg to 41 AE 10 mmHg (P > 0.30). Preliminary dose-ranging studies using doses of m-CPP (0.1 -1.0 mg=kg; n ¼ 3), TFMPP (0.3 -3.0 mg=kg; n ¼ 3) and quipazine (0.3 -3.0 mg=kg; n ¼ 3) known to induce erection in conscious rats 3 indicated that m-CPP was the only drug to elicit CN and ICP responses in anesthetized rats at doses producing erection in conscious rats (data not shown).…”
Section: Agonist Induced Intracavernous Pressure Responsesmentioning
confidence: 58%
“…12 TFMPP, quipazine and m-CPP display similar affinity for 5-HT 2c receptors and, similar potency and efficacy in stimulating IP 3 turnover in rat choroid plexus in vitro (a bioassay for 5-HT 2c agonists). 13 We have conducted an analysis of data presented by Hoyer et al 10 and Bonhaus et al 14 and have determined a strong correlation for the in vivo and in vitro potency of agonists and antagonists at 5-HT 2a =5-HT 2c receptors and binding affinities at native and cloned human and rat 5-HT 2a =5-HT 2c receptors (r ¼ 0.96-0.98; n ¼ 7; t ¼ 7.8 -15.3, t (0.05,5) ¼ 2.571; P < 0.001). Therefore, although complete dose -response curves were not examined in this study, doses were selected based on known in vivo and in vitro potency and selectivity at the various receptor subtypes and, preliminary experiments.…”
Section: Discussionmentioning
confidence: 99%